2020
DOI: 10.1021/acs.langmuir.0c01560
|View full text |Cite
|
Sign up to set email alerts
|

Taming the Coffee Ring Effect: Enhanced Thermal Control as a Method for Thin-Film Nanopatterning

Abstract: Predicting and controlling a droplet’s behavior on surfaces is very complex due to several factors affecting its nature. These factors play a crucial role in colloidal material deposition and related solution-based manufacturing methods such as printing. A better understanding of the processes governing the droplet in the picoliter regime is needed to help develop novel thin-film manufacturing methods and improve the current ones. This study introduces the substrate temperature as a method to control the dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…During the evaporation of a droplet on a substrate, a deposit of concentrated particles often tends to appear in the form of a ring-shaped pattern that is commonly referred to as the “coffee ring”. This coffee ring effect was first introduced by Deegan R. D. et al [ 47 ], and this phenomenon has been thoroughly studied both experimentally and theoretically in order to find the determining factors that provide control over the patterns composed of deposited particles [ 48 ]. The application of the coffee ring effect has already had an impact on various fields, such as DNA/RNA microarrays, nanoparticle assembly, and biophysical detection [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the evaporation of a droplet on a substrate, a deposit of concentrated particles often tends to appear in the form of a ring-shaped pattern that is commonly referred to as the “coffee ring”. This coffee ring effect was first introduced by Deegan R. D. et al [ 47 ], and this phenomenon has been thoroughly studied both experimentally and theoretically in order to find the determining factors that provide control over the patterns composed of deposited particles [ 48 ]. The application of the coffee ring effect has already had an impact on various fields, such as DNA/RNA microarrays, nanoparticle assembly, and biophysical detection [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to print a smooth and uniform line with uniform edges by controlling the drop frequency, temperature, and spacing, as reported by [231]. Recently, a study by Sliz et al [233] showed both experimentally and through simulation modeling that droplet behavior can be controlled by the substrate's temperature, thus controlling the coffee-ring effect. They showed that up to a critical temperature, an increase in heat transfer causes an increase in the capillary effect, and consequently, an increase in the size of the coffee-ring effect.…”
Section: Challenges and Limitationsmentioning
confidence: 91%
“…One obstacle lies in the nonuniformity of extrusion-printed active layers, owing to the directional mass transport within the printed droplets that is driven by the capillary flow during solvent evaporation ( 27 , 28 ). A second challenge is the creation of repeatable and stable polymer-metal junctions between the active layer and the cathode using the 3D printing approach at room temperature ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%